Long-term outcome of paediatric-onset multiple sclerosis: a population-based study. Issue 2 (15th November 2012) - Harding, Katharine E; Liang, Kate; Cossburn, Mark D; Ingram, Gillian; Hirst, Claire L; Pickersgill, Trevor P; Te Water Naude, Johann; Wardle, Mark; Ben-Shlomo, Yoav; Robertson, Neil P
Abstract : Background: Age of onset of multiple sclerosis (MS) peaks in the 3rd and 4th decades and is rarely less than 18. Robust longitudinal studies in paediatric-onset MS (POMS) are limited, and a clearer understanding of outcome could optimise management strategies. Methods: Patients with disease onset <18 years were identified from a prospective population-based register. Clinical features including presenting symptoms, time to Expanded Disability Status Scale (EDSS) 4.0, 6.0 and 8.0 and onset of secondary progression were compared with patients with adult-onset MS (AOMS). Results: 111 POMS patients were identified from a cohort of 2068. No significant differences in sex ratio, familial recurrence, relapse rate, ethnicity or clinical symptoms at presentation were identified between POMS and AOMS. However, interval to second relapse was longer (5 vs 2.6 years, p=0.04) and primary progressive disease was less common (0.9% vs 8.5%, p=0.003) in POMS than in AOMS. POMS patients also took longer to develop secondary progressive disease (32 vs 18 years, p=0.0001) and to reach disability milestones (EDSS 4.0, 23.8 vs 15.5 years, p<0.0001; EDSS 6.0, 30.8 vs 20.4 years, p<0.0001; EDSS 8.0, 44.7 vs 39 years, p=0.02), but did so between 7.0 and 12 years younger than in AOMS. Conclusions: 5.4% of patients with MS have POMS (2.7% <16 years; 0.3% <10 years) and have distinct phenotypic characteristics in early disease. Furthermore, while patients with POMS take longer to reach disability milestones, they do so at a younger age than their adult counterparts and could be considered to have a poorer prognosis. Management strategies for these patients should take account of these data.